Epidemiología de la sepsis en unidades de cuidado intensivo en Colombia (2016)
Severe sepsis and septic shock are important causes of morbidity and mortality in patients admitted to intensive care units (ICU).(1) These conditions are generally associated with multiple organ failure as a final outcome.(1-4) Over the past 30 years, the worldwide incidence of sepsis has increased by 13.7% per year.(1-4) It is therefore estimated that more than 18 million people suffer from sepsis each year, and more than five million of them die.(1-4) This increase is arguably due to the increasing numbers of people aged over 65 years (60% of septic patients are more than 65 years old), more frequent diseases and therapies causing immunosuppression, and the widespread use of diagnostic and/or therapeutic invasive procedures. Recent studies from Europe, the United Kingdom, Australia, and New Zealand have shown the incidence rates of sepsis and its mortality in ICUs.(5-9) North American studies are limited to data obtained in four Canadian ICUs that participated in a multinational study and to data taken from administrative databases.(1) These data reveal an incidence of sepsis in the ICU ranging from 11.8% to 37.4%, with mortality rates between 35% and 53.6% (both in the hospital and after 30 days).